Brand Image Analysis on Le Minerale Product Purchase Decisions: A Qualitative Study on Students in Makassar City - Seppa, Yusi irensi; Aslinda, Andi (Universitas Negeri Makassar, 2025)
Brand image is formed when consumers respond to differences between brands that result in a purchase decision. This study aims to find out the analysis of brand image on the purchase decision of Le Minerale products: Qualitative study in students in the city of Makassar. The type of research used is a qualitative descriptive approach that can help researchers by explaining the reality in the field. Data collection techniques are in the form of observation, interviews, and documentation. Data analysis techniques in the form of case studies include data collection, testing, categorization, and combining various data. A collective case study was conducted to draw conclusions or generalizations on the phenomenon of the case. The results of the study show that the positive image of the Le Minerale brand provides benefits for the company to be better known by consumers. Consumers will make purchasing decisions to buy products that have a good image. The company's image is based on the trust and reality of the company that produces quality Le Minerale Brand bottled water. Product image with consumer knowledge of the product and good impression. Consumer knowledge to know the easily recognizable characteristics of Le Minerale products. The image of the user from the user's impression of the product. Good impressions from consumers include the taste in the product that is a characteristic of the sweetness, namely the sweetness that is easy to remember and attached to the consumer's mind, as well as the impression of product quality. The purchase decision structure explains that product selection can be seen from satisfaction and confidence in choosing products, product selection can be seen from the firmness of choosing brands, the selection of purchasing channels can be seen from the decision in determining product providers, purchase time can be seen from determining when to buy products, and payment methods.